2022
DOI: 10.1038/s41390-022-02132-6
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of asymmetric dimethylarginine and homocysteine in epileptic children receiving antiepileptic drugs

Abstract: Background Epilepsy is a neurological disease that requires long-term antiepileptic drugs (AEDs). The old generation of AEDs may affect serum homocysteine and asymmetric dimethylarginine (ADMA) and disturb lipid levels. The aim of the study was to evaluate serum ADMA, homocysteine, lipid profile, and carotid intima-media thickness (CIMT) in epileptic children. Methods This study was implemented on 159 epileptic children who were subdivided into 3 subgroups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A meta-regression analysis was used to identify the source of heterogeneity among studies. Publication biases were assessed by Egger's tests (Stata 16.0) [20]. Two-sidedP < 0.05 was considered statistically signifcant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-regression analysis was used to identify the source of heterogeneity among studies. Publication biases were assessed by Egger's tests (Stata 16.0) [20]. Two-sidedP < 0.05 was considered statistically signifcant.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with older AEDs, these new AEDs are less likely to infuence hepatic enzymes [9] and are supposed to be less likely to disrupt Hcy metabolism [10]. In recent years, some case-control studies have been conducted to explore the correlation between Hcy and new AEDs [11][12][13][14][15][16][17][18][19][20]. In a case study, Sun et al argued that the new AEDS do not cause elevated blood ammonia and Hcy levels, so they have high drug safety.…”
Section: Introductionmentioning
confidence: 99%
“…Epileptic children receiving VPA were characterized by a simultaneous increase in ADMA and HCys concentrations compared to controls [ 7 ]. The latest research by Mahmoud et al [ 19 ] found that long-term use of AEDs can increase lipid profiles, homocysteine, and ADMA levels. The authors also observed that this effect is particularly noticeable in the case of polytherapy with old-generation drugs, while in the case of new AEDs, a minimal effect was observed.…”
Section: Discussionmentioning
confidence: 99%
“…The authors also observed that this effect is particularly noticeable in the case of polytherapy with old-generation drugs, while in the case of new AEDs, a minimal effect was observed. [ 19 ].…”
Section: Discussionmentioning
confidence: 99%